PENYUTRADARAAN FILM FIKSI PANDORA TANARA MENGGUNAKAN RITME INTERNAL UNTUK MEWUJUDKAN SUSPENSE - Ani Marshella Johan; Zainal Abidin; Dynia Fitri (Institut Seni Indonesia Padang Panjang, 2023)
Film is the right medium to convey messages to the wider community. Pandora Tanara is a fictional trailer genre film with duration 30 minutes. The film Pandora Tanara tells the story of a psychopathic mother who locks up her child and gives her drugs. The dynamic narrative structure and conflicts contained in the Pandora Tanara film scenario are manifested in internal rhythms to create tension. Internal rhythm is applied by paying attention to image movement, player movement, type of shot and sound, to create suspense in the film. Image cuts that adjust the rhythm of the character scenes in the film, as well as the selection of shots and sound effects. The purpose of creating this work is to create tension by using aspects that exist in internal rhythms.